Macular Pigment Optical Density in Chinese Primary Open Angle Glaucoma Using the One-Wavelength Reflectometry Method - Yuying Ji; Chengguo Zuo; Mingkai Lin; Xiongze Zhang; Miaoling Li; Lan Mi; Bing Liu; Feng Wen (Journal of Ophthalmology)
Purpose. To investigate macular pigment optical density (MPOD) and its relationship with retinal thickness in primary open angle glaucoma (POAG) patients using the one-wavelength reflectometry method. Methods. A total of 30 eyes from 30 POAG patients (18 males and 12 females, mean age 47.27±16.93) and 52 eyes from 52 controls (27 males and 25 females, mean age 49.54±19.15) were included in this prospective, observational, case-control study. MPOD was measured in a 7-degree area using one-wavelength reflectometry method. Two parameters, max and mean optical density (OD), were used for analyses. Spectral-domain-optical coherence tomography was used to measure retinal thickness, including central retinal thickness (CRT), the macular ganglion cell complex (GCC), and the circumpapillary retinal nerve fiber layer (RNFL). Results. Both maxOD and meanOD were significantly reduced in POAG patients compared with normal subjects (P<0.001). GCC, CRT, and RNFL thicknesses were also significantly reduced in POAG patients (P<0.001). GCC thickness had a positive relationship with MPOD. Conclusions. MPOD within the 7-degree area was significantly lower in Chinese POAG patients than in control subjects, and GCC thickness was significantly and positively associated with MPOD. Whether the observed lower MPOD in POAG contributes to the disease process or is secondary to pathological changes caused by the disease (such as loss of ganglion cells) warrants further and longitudinal study.